EFFECT OF EMPLOYEE RESPONSIBILITY AND ABILITY THROUGH WORK ACHIEVEMENT ON EMPLOYEE PERFORMANCE ON BP BATAM - Susanto Dwi Handoko; Zulkifli Eko Purwanto; Muammar Khaddafi; Sheptya Yusnita Putri; Rusdin Haluddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The influence of responsibilities and abilities of employees through job performance on employee performance. The research was conducted at the Batam Concession Agency, with the consideration that BP Batam is a government agency mandated for the management of existing resources on Batam Island with various line units, and is required to provide excellent service. This study aims to see and analyze the influence of leadership responsibility factors and incentives on employee performance in BP Batam. This study aims to analyze the factors that affect the performance of BP Batam. The sample used is as many as 65 respondents from 70 employees. The method used in this research is quantitative research and the type of research used is explanatory research or explanation. The data analysis method used is the Structural Equation Model (SEM-PLS). Based on the data analysis, the results show that responsibility does not have a significant effect on work performance (original sample value is 0.389 and P value is 0.110> 0.07) and responsibility has a significant effect on employee performance (original sample value - 0.397 and p value is 0.002. <0.07). Employee ability has a positive and significant effect on work performance (original sample value 0.397 and P value 0.003 <0.07). Employee ability does not have a positive and significant effect on employee performance (original sample value 0.466 and value 0.112> 0.07).